EXPERIMENTAL RESEARCH OF ROD TURNING MACHINE NOISE - T.A. Finochenko; A.N. CHUKARIN (Advanced Engineering Research)
Experimental noise research was held in mechanical shops conditions. The noise research demonstrated exceeding of norms by 6-20 Db on the sound pressure levels in the zone of frequencies of 250-8000 Hz for turning-revolving lathes.